EKSISTENSI TRADISI “MAPPATETTONG BOLA” MASYARAKAT SUKU BUGIS DESA ANABANUA KECAMATAN BARRU KABUPATEN BARRU DALAM PERSPEKTIF HUKUM ISLAM - Muh. Sudirma; Mustaring Mustaring; Rinda Muliati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
This article describes the research on the existence of the “Mappatettong Bola” tradition of the Bugis tribe in Anabanua Village, Barru District, Barru Regency in Islamic Law Perspective. This study uses data collection techniques by making observations, interviews, and documentation. The data that has been obtained from the research results are processed using qualitative descriptive analysis. The results showed that (1) the tradition of "Mappatettong Bola" means establishing a typical Bugis stilt house frame with various stages starting from determining the place and time, the ritual participants namely Panrita Bola, and the local community, followed by the Lise Posi Bola ritual which became the foundation for the initial establishment of the framework. house on stilts (2) the values ​​contained in the “Mappatettong Bola” tradition such as the value of mutual cooperation, and religious values ​​are still there and are carried out by the community to this day. (3) The implementation of this tradition has positive values ​​that are not against the teachings of the Islamic religion, because society does not make spirits or supernatural beings to mediate the relationship between humans and God. Ritual Lise 'Posi' The ball in the middle of the house (posi'bola) is a sacred thing, and is a symbol of a sense of hope and optimism (assennu-sennureng) for something that is good without being excessive and not related to aqidah. In addition, there is a religious value in the form of Barazanji reading and implementation of this tradition which has a good value, namely uniting the community, relatives and neighbors which is highly recommended in Islam. As well as the implementation intention also contains prayers to the Almighty to ask for protection and safety in the implementation of this tradition.